1996
DOI: 10.2135/cropsci1996.0011183x003600010022x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins in Enhanced Growth and Tillering of Wheat Induced by Mixed Nitrogen Source

Abstract: Supplying wheat plants with mixtures of NO~-and NH4 + increases growth and tiller production, but the physiological basis is unclear. Our objectives were to evaluate the roles for cytokinins and N use (e.g., accumulation, distribution, and utilization of absorbed N to produce tillers) in eliciting this response. Two species of spring wheat (Triticum aestivum L. cv. Len and Triticum durum Desf. cv. Inbar) were grown hydroponically in the greenhouse with N supplied as all NO~-, all NH4 + , or an equal mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 0 publications
4
29
0
5
Order By: Relevance
“…This is in accordance with the fact that in high nutrient concentration situations the general trend is a decrease in root length and number of ramification at excessive nutrient supply. The most common response to an increase in nitrate and ammonium concentration in the environment is a decrease in root : shoot ratio (Boxman et al 1991;Wang and Below 1996;Bauer and Berntson 1999) and a decrease in fine : coarse root ratio (Haynes and Goh 1978;Boxman et al 1991;Britto and Kronzucker 2006), as observed here.…”
Section: Discussionsupporting
confidence: 70%
“…This is in accordance with the fact that in high nutrient concentration situations the general trend is a decrease in root length and number of ramification at excessive nutrient supply. The most common response to an increase in nitrate and ammonium concentration in the environment is a decrease in root : shoot ratio (Boxman et al 1991;Wang and Below 1996;Bauer and Berntson 1999) and a decrease in fine : coarse root ratio (Haynes and Goh 1978;Boxman et al 1991;Britto and Kronzucker 2006), as observed here.…”
Section: Discussionsupporting
confidence: 70%
“…A giberelina, porque pode alterar o alongamento celular em função de efeitos da qualidade da luz (WELLER et al, 1994;FOSTER et al, 1994;LÓPEZ-JUEZ et al, 1995;REED et al, 1996) e a citocinina por estimular a iniciação da divisão celular em afilhos (WANG & BELOW, 1996). Outra possibilidade é o fato de o fitocromo estar envolvido no controle de genes ligados à fotossíntese, codificando a síntese de clorofila a/b, pequenas subunidades da Rubisco e outros componentes do maquinário fotossintético (DALE, 1988).…”
Section: Resultsunclassified
“…Moreover, it is found that there is a marked difference among N forms in their effects on growth and chemical composition of crop plants (Cramer and Lewis 1993). The physiological processes in plants, such as root respiration (Matsumoto and Tamura 1981), photosynthesis (Shelp and Taylor 1990), and secondary metabolism (Wang and Below 1996) are also dramatically associated with N form. Thus it is possible that Cd uptake and translocation in the plants will be affected by N form in the nutrient medium.…”
Section: Introductionmentioning
confidence: 99%